C-Reactive Protein and other Hematological parameters for diagnosis of Neonatal Sepsis - Umesh Patel; Vishnu Kumar Patel; Narmada Prasad Patel; Jyotsna Verma; Bhupendra Kumar Ratre; S.P. Verma (International Journal of Medical Research and Review, 2014)
Background: Sepsis is one of the most common causes of morbidity and mortality in the newborn. Early diagnosis and treatment is vital to improve outcome. The present study was therefore carried out to determine the usefulness of C-reactive protein (CRP) for evaluation of neonatal sepsis in teaching hospital of central India.Method: 82 neonates with clinical suspicion of sepsis were prospectively studied over a 12 month period. Blood was obtained from each subject recruited for the qualitative estimation of CRP. Blood culture was used as gold standard for diagnosis of NNS.Results: Of 82 neonates studied, 67 (81.7%) had positive CRP while 58 (70.73%) had positive blood culture. The sensitivity, specificity, positive and negative predictive values and diagnostic accuracy of CRP were 81.7%, 88.0%, 95.7%, 59.5% and 83.2%. respectively.Conclusion: The qualitative method of estimating CRP which is cheap and rapid has moderate sensitivity, specificity and negative predictive value. It is a good diagnostic test and can identify the infection in neonates at the time of initial assessment.